A review of Stratospheric Sounding Unit radiance observations for climate trends and reanalyses. (19th February 2015) - Nash, John; Saunders, Roger
<x xml:space="preserve">Abstract</x> Stratospheric Sounding Units (SSU) on the NOAA polar‐orbiting satellites measured infrared radiances in the 15 μm CO2 band between late 1978 and mid‐2006. From these radiances a time series of layer‐mean stratospheric temperatures has been derived by several groups. Discrepancies in these temperature analyses have been highlighted recently and efforts are now underway to resolve the differences between them. This article is the Met Office response summarising the issues to be resolved in creating a climate data record from the different SSUs, including corrections for radiometric, spectroscopic and tidal differences. Calibration issues identified include the SSU space‐view anomaly and radiometric anomalies in the NOAA‐9 observations. The spectroscopic correction required for changing pressures in the pressure modulator cells is also outlined. The most important correction for the time series is for the solar diurnal and semi‐diurnal tides as the satellite overpass local times change. Comparisons with other stratospheric temperature trend analyses are made and the reasons for the differences discussed. The time series presented here show sustained drops in stratospheric temperatures at all levels after the El Chichon and Pinatubo eruptions but only small trends to lower temperatures between eruptions.